CLUSTER HEADACHE - Michelle Anisa; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2022)
Cluster headache (CH) is a trigeminal autonomic cephalgia characterized by attacks of severe unilateral headache accompanied by ipsilateral autonomic symptoms. The prevalence of cluster headache in the overall population is 1 in every 1000 people. The exact etiology of cluster headache remains unclear. However, it is thought that there is a connection between the trigeminovascular system, parasympathetic nerve fibers involved in trigeminal autonomic reflexes, and the hypothalamus. Treatment of CH has three stages, namely: abortive, transitional, and preventive. Cluster headaches tend to subside with age with less frequent attacks and longer periods of remission between attacks.